Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Pendidikan Agama Islam di UPTD SMP Negeri 30 Padang - Bustami Bustami; Syafruddin Nurdin; Muhammad Kosim (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research aims to analyze the implementation of the independent learning curriculum in PAI subjects at UPTD SMP Negeri 30 Padang. Researchers use field research (Field Research) as a type of research in areas located in the community which are descriptive qualitative in nature. Primary data sources include the principal, deputy principal, educators, and students at UPTD SMP Negeri 30 Padang using the Snowball sampling technique in determining informants. Secondary data was obtained through archives regarding the implementation of the independent learning curriculum in PAI subjects at UPTD SMP Negeri 30 Padang. Data collection techniques using observation, interviews and documentation. Data analysis technique that uses three activity lines, namely: reducing data, presenting it, and drawing conclusions. The results of the analysis in this research are that the implementation of the Merdeka Curriculum in the subjects of Islamic Religious Education and Character at UPTD SMP Negeri 30 Padang has the following provisions: it is considered very good and in accordance with the provisions of the guidelines for its implementation.